A Labor of (Queer) Love: Maintaining "Cozy Wholesomeness" on Twitch During COVID-19 and Beyond. (July 2022) - Youngblood, Jordan
This article explores the idea of "cozy wholesomeness" in streaming on the Twitch platform through the example of an LGBTQ+ content creator, her partner, and her development of an ongoing domestic space which welcomed queer audiences during the COVID-19 pandemic. Focusing on a span of streams from November 2020 to January 2021, the article first seeks to define cozy wholesomeness as a streaming process that combines choice of game, style of streaming, and audience interest to form an experience driven by intimacy, sincerity, and active resistance to alt-right mentalities even as the concept itself potentially becomes a product or marketing hook. For this particular streamer, producing a supportive, active chat community driven by cozy wholesomeness inevitably collides with sustaining streaming as a profitable venture—a process compounded by Twitch's own interest in commoditizing queer content as a way of displaying its own apparent diversity.